COVID-19 vaccination acceptance and adherence among pregnant and lactating high-risk group individuals of Maharashtra State, India - Vaibhav Kumar; Yashashree Patil; Romi Jain; Nikhil Bhanushali; Ketaki Gaonkar; Jobsy Ciby (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Since the outbreak of the pandemic, the release of the COVID (Corona Virus Disease)-19 vaccine was highly anticipated. Nevertheless, vaccine availability does not symbolize the end of pandemic due to ongoing vaccine hesitancy and anti-vaccination movements. The objective of this study is to evaluate COVID-19 vaccine acceptance among pregnant and lactating individuals in Maharashtra state, India. MATERIALS AND METHODS: A descriptive cross-sectional study was conducted via a hybrid approach using various digital portals such as Whatsapp, telegram, and physical distribution to those who did not have access to smartphone devices. A probability proportional sampling strategy was deployed. A pre-validated structured self-administered questionnaire tool designed by Freeman et al. 2020 (Oxford COVID-19 vaccine hesitancy scale) was used, which consisted of seven close-ended targeted and focused questions. Analysis of several survey items and vaccine acceptance was conducted using the Chi-square test. RESULTS: Analysis revealed that 58% of individuals were willing to take vaccines after government approval and 26% of individuals showed hesitancy toward vaccination. When compared, lactating individuals showed less vaccine hesitancy (22%) than pregnant individuals (27%). The maximum vaccine hesitancy was observed in the third trimester of pregnancy (29.5%). CONCLUSIONS: Trust in vaccines is a crucial factor and is dependent on the ability of the government in promoting vaccines through effective communication; this can be one of the reasons for the high level of acceptance and awareness toward COVID-19 vaccination in this study.